Avaliação da expressão de genes relacionados ao reparo de danos em fita dupla no DNA de pacientes com leucemia mielóide crônica com e sem uso de inibidores de tirosino-quinase - Maia Filho, Pedro Aurio (2023)
Chronic myeloid leukemia (CML) originates from a clonal disorder where massive expansion of neoplastic cells of the myeloid lineage occurs. The characteristic genetic alteration of CML is the Philadelphia chromosome (Ph), which results from a reciprocal translocation between the long arms of chromosomes 9 and 22, generating a BCR-ABL oncoprotein with constitutively activated tyrosine kinase activity. The treatment of choice for patients in the chronic phase of the disease are tyrosine kinase inhibitors. DNA damage repair is essential to ensure genome integrity. It is known that double-stranded damage (DSB) is more damaging to DNA, and may trigger genomic instability and predisposition to cancer. In mammals, the major repair pathway for DSBs is non-homologous end joining (NHEJ). In this context, we propose to evaluate the expression of genes related to DSB repair in the DNA (ATM. XRCC5, XRCC6 and LIG4) of patients with CML, through the NHEJ pathway, and the influence of the chronic use of TKIs on the expression of these genes. This is a cross-sectional study with 91 patients with a clinical and molecular diagnosis of CML, 59 (64.8%) using first-generation ITK (G1 CML), 26 (28.6%) using second generation (G2 CML) and 6 (6.6%) at diagnosis/without treatment (D CML). The control group (CG) of healthy individuals was composed of 20 blood donors. Gene expression analysis was performed by real-time polymerase chain reaction. Statistical analysis was performed using the GraphPad Prism 6.0 program, the tests performed were determined according to the normality of the data. The significance level used was 5% (α ≤ 0.05). Comparisons of gene expression related to DNA repair in patients with CML and CG showed statistically higher values of genes XRCC5 and XRCC6 in the group of patients with CML. Comparisons of ATM and LIG4 genes (CML versus CG) showed no statistical differences. By stratifying the patients into three groups (D CML, G1 CML and G2 CML), it was found that the group of patients with CML at diagnosis/without treatment (D CML) had higher levels of ATM gene expression compared to the others groups. Statistical differences were verified in the following comparisons: D CML versus CG CML, D CML versus G1 CML and D CML versus G2 CML. When analyzing the expression of the XRCC5 and XRCC6 genes in the groups of the present study, the results found were similar for both genes. In the case of the XRCC5 gene, there was a statistically significant increase in expression levels in patients from the G1 CML and G2 CML groups in relation to patients at diagnosis/without treatment (D CML D) and CG. The results for XRCC6 differ only in the comparison: G2 CML versus CG and G2 CML versus D CML, where there was no statistical difference, even the expression levels of the XRCC6 gene being very high in relation to the D CML and CG groups. There was no statistical difference when comparing the expression of the LIG4 gene in the groups of the present study. Comparing the level of molecular response (MR) in patients with CML using imatinib, an increased expression of the XRCC5 and XRCC6 genes was observed in the group WITH MR compared to the groups WITHOUT MR and CG. Comparisons of the expression of the ATM, XRCC5, XRCC6 and LIG4 genes with the risks of the Sokal, Hasford, Eutos and ELTS scores did not show statistical differences. These findings suggest that ATM is increased in the early stages of the disease, XRCC5 and XRCC6 are unfavorable prognostic markers, and that LIG4 does not play a role as a potential prognostic marker in patients with CML. Furthermore, imatinib probably increases the expression of the XRCC5 and XRCC6 genes in patients with CML, but does not seem to influence the expression of the ATM and LIG4 genes.